COVID-19 DEATHS AMONG THE ELDERLY IN A MUNICIPALITY IN NORTHWESTERN PARANÁ, BETWEEN THE YEARS 2020 AND 2021 - Quevedo dos Santos, Natália; Franciele Toldo de Toledo, Karine; Maria Marque Gomes Bertolini, Sônia (Arquivos do Mudi, 2023)
In December 2019, a new virus called SARS-CoV-2 was identified. The World Health Organization (WHO) named the disease caused by the new virus COVID-19 (coronavirus disease, year 2019), and in March 2020, it was declared a pandemic. Since then, there has been a global effort to produce information in order to unravel the clinical, epidemiological, and prognostic factors of the disease. By identifying the main risk factors, it is possible to carry out early monitoring of the most vulnerable groups, reducing the chance of unfavorable clinical outcomes. It is a consensus that advanced age is associated with an increase in morbidity and mortality. This study aimed to verify the occurrence of COVID-19 deaths among the elderly in the city of Maringá, Paraná, in the years 2020 and 2021, as well as their association with gender. This research is characterized as a retrospective quantitative study. The data were obtained from the Notifiable Diseases Information System (Sinan). The dependent variable was the occurrence of death in elderly patients, and the independent variables were gender and year of occurrence. Descriptive and inferential statistics were used to analyze the data. Results showed that in 2020, there were 514 deaths (40.5% female and 59.5% male). In 2021, the number of deaths increased exponentially, reaching 2025 cases (39.6% female and 60.4% male). The highest occurrence of COVID-19 deaths among the elderly occurred in 2021 and in males. Based on this profile, specific strategies and care lines should be studied for this more vulnerable population in times of pandemics.